PEMBERIAN DAUN Crotalaria usaramoensis SEBAGAI SUMBER PROTEIN RANSUM BURUNG PUYUH PERIODE GROWER TERHADAP ENERGI METABOLIS, RETENSI NITROGEN DAN EFISIENSI RANSUM - Dianti, Rostika; Mulyono, Mulyono; Wahyono, Fajar (Animal Agriculture Journal, 2012)
The purpose of this study was to determine the effect of leaf C.usaramoensis with different percentage rate period quail grower diet for metabolicenergy, protein retention and diet efficiency. The material used in the study werefemale quail age of three weeks with an average body weight of 49,55 g ± 2.69with the amount 100 quail. Diet composed of three materials consist of wheat leafC. usaramoensis, concentrate of Charoen Pokpand and yellow corn. Diet researchcompiled by ± 24% protein content and metabolic energy ± 3000 kcal / kg. Thedesign used was completely randomized design with 4 treatments and 5replications and 5 tail quail for each experimental unit. Treatment research is T0(diet without leaf C. usaramoensis), T1 (diet with 3% leaf C. usaramoensis), T2(diet with 6% with leaf C. usaramoensis) and T3 (diet with 9% with leaf C.usaramoensis). Parameters measured were diet consumption, body weight,metabolic energy, nitrogen retention and diet efficiency. Processing data usinganalysis of variance to determine the effect of various treatments. The resultsshowed no significant difference (P> 0.05) due to the provision of leaf C.usaramoensis on metabolic energy, nitrogen retention and diet efficiency. Basedon the results of research on the provision of leaf C. usaramoensis to 9% the sameas the diet control so that leaf C. usaramoensis can be used as an alternativesource of protein feed ingredients in the diet quail.Key words : Crotalaria usaramoensis, metabolic energy, nitrogen retention, dietefficiency